2007
DOI: 10.1007/s10194-007-0421-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of spontaneous intracranial hypotension in the emergency department

Abstract: Spontaneous intracranial hypotension is considered a rare disorder. We conducted a study on the frequency of spontaneous intracranial hypotension in the emergency department (ED). We identified patients with spontaneous intracranial hypotension evaluated in the ED of a large urban hospital between 1 January 2003 and 31 December 2006. For comparison, we also identified all patients with spontaneous subarachnoid haemorrhage (SAH). Eleven patients with previously undiagnosed spontaneous intracranial hypotension w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 10 publications
1
73
0
3
Order By: Relevance
“…The annual incidence has been estimated as 5 per 100,000. 16 Orthostatic headache is the most common, but not mandatory, manifestation of IHS, accompanied by a wide variety of other symptoms such as neck pain or stiffness, nausea, hearing loss, visual blur- ring, facial numbness, Parkinsonism, ataxia, or dementia. 2,9,17 It seems plausible that a low CSF volume due to a persistent CSF leak is the cause of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The annual incidence has been estimated as 5 per 100,000. 16 Orthostatic headache is the most common, but not mandatory, manifestation of IHS, accompanied by a wide variety of other symptoms such as neck pain or stiffness, nausea, hearing loss, visual blur- ring, facial numbness, Parkinsonism, ataxia, or dementia. 2,9,17 It seems plausible that a low CSF volume due to a persistent CSF leak is the cause of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A 4-year observation study of a large urban ED identified 11 confirmed cases of SIH, none of which were diagnosed in the ED. 3 The general accepted mechanism of SIH is CSF leakage rather than low CSF production. Leakages of CSF occur through defects in the dura mater.…”
Section: Discussionmentioning
confidence: 99%
“…Small studies report that SIH is often misdiagnosed in the ED mainly due to lack of awareness of the condition. 3 …”
mentioning
confidence: 99%
“…CT scan should contribute to diagnostic resolution. Rest and hydration are the treatment of choice in most of these cases; in only a few is neurosurgery required [31].…”
Section: Intracranial Hypotensionmentioning
confidence: 99%